Domestication rewired gene expression and nucleotide diversity patterns in tomato. (12th June 2017) - Sauvage, Christopher; Rau, Andrea; Aichholz, Charlotte; Chadoeuf, Joël; Sarah, Gautier; Ruiz, Manuel; Santoni, Sylvain; Causse, Mathilde; David, Jacques; Glémin, Sylvain
Summary: Plant domestication has led to considerable phenotypic modifications from wild species to modern varieties. However, although changes in key traits have been well documented, less is known about the underlying molecular mechanisms, such as the reduction of molecular diversity or global gene co‐expression patterns. In this study, we used a combination of gene expression and population genetics in wild and crop tomato to decipher the footprints of domestication. We found a set of 1729 differentially expressed genes (DEG) between the two genetic groups, belonging to 17 clusters of co‐expressed DEG, suggesting that domestication affected not only individual genes but also regulatory networks. Five co‐expression clusters were enriched in functional terms involving carbohydrate metabolism or epigenetic regulation of gene expression. We detected differences in nucleotide diversity between the crop and wild groups specific to DEG. Our study provides an extensive profiling of the rewiring of gene co‐expression induced by the domestication syndrome in one of the main crop species. Significance Statement: Plant domestication is known to have affected patterns of genome diversity, but its impact on gene expression levels remains poorly understood. Here, using high‐throughput sequencing, our comparative genomics approach revealed the underlying rewiring of gene co‐expression patterns in tomato due to domestication, as well as the associated biological functions and loss of nucleotide diversity.